Pengaruh Pemberian Pupuk Organik Nasa dan Zat Pengatur Tumbuh Atonik terhadap Pertumbuhan dan Hasil Kacang Tanah (Arachis hypogaea L.) - Ainun Marliah; Nurhayati Nurhayati; Herita Mutia (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
Effect of Concentration Nasa Organic Liquid Fertilizer and Growth Regulator Atonic and Plant Growth and Yield and Yield Ground PeanutABSTRACT. The aim of this research was to study effect on Nasa organic fertilizer concentration and atonik growth regulator on growth and yield ground peanut. The experimental design was completely block randomized design with two factor and three replications. The two factor investigated were Nasa liquid organic fertilizer concentration (1 ml/l, 2 ml/l, 3 ml/l of water) and Atonik growth regulator concentration (1 ml/l, 2 ml/l, 3 ml/l of water). Result showed that Nasa organic liquid fertilizer concentration highly significant different affected on plant height 45 and 60 days after planting and significant different on dry seed weight per plot netto and 100 g dry seed. The best result of Nasa liquid organic fertilizer concentration was 3 ml/l. Atonik growth regulator concentration showed highly significant different effect on plant height 60 DAP and significant effect on plant height 45 DAP. The best Atonik concentration was 3 ml/l. There was a correlation between Nasa organic fertilizer concentration and Atonik growth regulator on plant height 45 DAP.